Pembuatan Motion Graphics SOP Produksi Berita sebagai Media Promosi di PT Bintang Advis Multimedia - Sagala, Siti Haminah; Nugraha, Ivan; Siskandar, Ridwan (PUSAT SAINS INDONESIA, 2020)
The more infotainment news programs in Indonesia, the production house companies are competing to produce news programs that are much in demand by the public. One of the infotainment news programs is Halo Selebriti. Halo Selebriti is an infotainment program produced by PT Bintang Advis Multimedia. To produce news programs that are of interest to the public, an attractive and informative promotional media is needed about the Halo Selebriti explanation. The purpose of this project is to produce an attractive and informative promotional media so that it can convey information about Halo Selebriti which is packaged in the form of motion graphics using Adobe Illustrator, Adobe After Effects, Adobe Audition, Adobe Premiere Pro and Adobe Media Encorder.